A NEW SPECIES OF DEPARIA FROM NEW GUINEA - Wita Wardani; Jaenudin Jaenudin; Ismail Apandi; Anne Kusumawaty; Wahyudi Santoso (Reinwardtia, 2021)
WARDANI, W., JAENUDIN, APANDI, I., KUSUMAWATY, A. & SANTOSO, W. 2021. A new species of Deparia from New Guinea. Reinwardtia 20(2): 57−61. — Deparia stellata is a new species of highland in Eastern New Guinea, described from a specimen found among unidentified piles of New Guinean Expedition in 1975. Its distinctive stellate-hairs on all axis and occasionally on rachis-scale margin are the main character that differentiate the species to other Deparia.